Uji Aktivitas Antipiretik Ekstrak Daun Bidara (Ziziphus Spina Christi L) Terhadap Mencit Jantan (Mus Musculus) - Ferdinan Jalung; Mila Febrina Rindayani; Meity Christiani (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background; Indonesia has thousands of types of plants spread across various regions. The existing biodiversity can be used as raw material for modern and traditional medicines. Indonesian people have long known and used traditional medicine to treat various diseases. The increasingly expensive price of modern medicine on the market is one reason to explore the use of traditional medicine again. Many types of medicinal plants in Indonesia have been used as raw materials for medicine, some of these plant species have even been clinically tested for their phytochemical content, efficacy and safety of use. Objectives; To find out that bidara leaf extract (Ziziphus spina-christi L.) has antipyretic activity. Method; This type of research is experimental research.Extraction is carried out to filter out polar compounds so 60% ethanol liquid is used. Results; From the results of research that has been carried out, it was found that the average difference in temperature reduction between time and fever temperature was from 30 minutes to 120 minutes. For doses of 100 mg/30 g, 150 mg/30 g BW of mice, 200mg/30 g BW of mice, NaCMC and Paracetamol at 30 minutes respectively were 0.27, 0.37, 0.44, 0 .04 and 0.8oC. For doses of 100 mg/30 g, 150 mg/30 g BW of mice, 200 mg/30 g BW of mice, NaCMC and Paracetamol at 60 minutes respectively were 0.6, 0.67, 0.94, 0.07 and 1.47oC. For doses of 100 mg/30 g, 150 mg/30 g BW of mice, 200 mg/30 g BW of mice, NaCMC and Paracetamol at 90 minutes respectively were 1.04, 1, 1.24, 0, 07 and 2.1oC. Conclusion; Bidara leaf extract (Ziziphus spina-christi L.) has antipyretic activity in mice. Bidara leaf extract (Ziziphus spina-christi L.) which has antipyretic activity is at a dose of 100 mg, 150 mg and 200 mg/30 grams of body weight for mice.